Poetic Allusion of J. Milton’s Poem “Paradise Lost” in Historical Discourse of W. Churchill - T. N. Zubakina (Научный диалог)
Literary allusion in historical discourse is considered as a means of enhancing the semantic and aestheticemotional content of the text. The results of studying the semantics of allusive units in the works of W. Churchill, taking into account the historical context of events are presented in the article. The results of a comparative analysis of three unidentified political allusions noted in D. Holly’s book “Churchill’s Literary Allusions” are discussed. The author of the publication emphasizes that when using the allusion as a unit of renomination, the context affects the creation of the allusive meaning. The variants of allusive meanings of the same lines of J. Milton’s poem “Paradise Lost” in three different historical contexts and different literary genres: in historical narration, in a public speech of a British politician and in military memoirs are analyzed in the article. The novelty of the study is seen primarily in the fact that the studied poetic allusions were not previously identified in the texts of W. Churchill. The value of the research results lies in its interdisciplinary nature, carried out at the intersection of linguistics, semantics, history and hermeneutics.